Analysis of Socio-Political Discourses in the Films of Srijit Mukherji - Yadav, Sudarshan; Roy, Wrishav (Journal of Advanced Research in Journalism & Mass Communication, 2022)
This article would be analyzing the selected films of Srijit Mukherji from the perspective of socio-political discourses/ issues presented in those films. Cinema is a literary form which acts as a medium to put forth the socio-political discourses for the public to think and reflect. These literary creations are mainly the reflections of the director of the film. The idea, theme and arguments put forth through the screen of cinema in the form of socio-political discourses become the part of the cinematic art. Thus, this paper analyses this aspect with reference to the nine prominent films of Srijit Mukherji, viz., Autograph, Baishe Shrabon, Hemlock Society, Jaatishwar, Chotushkone, Nirbaak, Rajkahini, Zulfiqur and Uma.